Human Anatomy: An Inlet of Medicine and Surgery - Abdelmonem Awad Hegazy (International Journal of Human Anatomy, 2019)
An educational essay frames human anatomy as foundational to medicine and surgery, highlighting learning modalities and integration with imaging and simulation.
Keywords: Human Anatomy